Analisis Event Study New Normal Terhadap Harga Saham di Bursa Efek Indonesia - Rica Yulianti Lukman; Kartini Kartini; Yohanis Rura (Politeknik Ganesha Medan, 2023)
This study aims to analyze abnormal returns before and after the announcement of the implementation of the new normal (vaccine) on manufacturing sector companies. The object of research is through the official website of the Indonesia Stock Exchange (IDX). Data collection by the documentation method collects data and information obtained from www.idx.co.id and www.finance.yohoo.com websites which contain the closing daily stock price and the number of stock trading transactions and the overall number of shares that are distributed at a certain time. The results showed that there was an abnormal difference in returns before and after the announcement of the implementation of the new normal in the manufacturing sector. The announcement of the implementation of the new normal in Indonesia contains information that is different from before. The second hypothesis shows that there was no significant difference in trading volume activity in the period before and after the announcement of the implementation of the new normal in the manufacturing sector. This illustrates that investors do not get signals related to existing information, because they do not give different reactions to trading volume activity.